Acute Porphyrias in the USA: Features of 108 Subjects from Porphyrias Consortium - Bonkovsky, Herbert L.; Maddukuri, Vinaya C.; Yazici, Cemal; Anderson, Karl E.; Bissell, D. Montgomery; Bloomer, Joseph R.; Phillips, John D.; Naik, Hetanshi; Peter, Inga; Baillargeon, Gwen; Bossi, Krista; Gandolfo, Laura; et al. (The American journal of medicine, 2014)
Recent descriptions of the clinical and laboratory features of subjects with acute porphyrias in the US are lacking. Our aim was to describe clinical, biochemical, and genetic features of 108 subjects. Between September 2010 and December 2012, 108 subjects with acute porphyrias (90 acute intermittent porphyrias, 9 hereditary coproporphyrias, 9 variegate porphyrias) were enrolled into an observational study. Genetic testing was performed at a central genetic testing laboratory and clinical information entered into a central database. Selected features were compared with data for adults in the US. Most subjects (88/108, 81%) were female, with self-reported onset of symptoms in the second through fourth decades of life. The most common symptom was abdominal pain. Appendectomies and cholecystectomies were common before a diagnosis of porphyria. The diagnosis was delayed by a mean of 15 years. Anxiety and depression were common, and 18% complained of chronic symptoms, especially neuropathic and other pains. The incidences of systemic arterial hypertension, chronic kidney disease, seizure disorders, and psychiatric conditions were markedly increased. Mutations of the known causative genes were found in 102/105 of those tested, with novel mutations being found in 37, including in 7/8 subjects with hereditary coproporphyria. Therapy with intravenous hematin was the most effective therapy both for treatment of acute attacks and for prevention of recurrent attacks. Acute porphyrias often remain undiagnosed for more than a decade after first symptoms develop. Intravenous hematin is the treatment of choice, both for treatment of acute attacks and for prevention of recurrent attacks.